The Influence of Taxpayer Awareness and Tax Sanctions on Compliance in Paying Land and Building Tax P-2 : Case Study of Pondok Melati Sub-District, Bekasi City - Chresensia Oppon Natasya Damanik; Juaniva Sidharta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
After Law Number 28 of 2009 pertaining to Regional Taxes and Regional Retributions was passed, the local administration is now able to collect local taxes in accordance with the plan. Finding out how taxpayer information and The purpose of this study is to determine how tax fines affect Pondok Melati District's adherence to land and construction tax payments. A review of the literature is utilized as evidence. This study employs quantitative methodologies, mostly through data collection via questionnaires. Multiple linear regression analysis is used to evaluate the data in this study. The study's findings indicate that while both elements have favorable and substantial effects at the same time, unpaid knowledge and tax sanctions have a partial and relatively high impact in Pondok Melati District for land and construction tax compliance.